PENERAPAN METODE GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) PADA KASUS PENYAKIT PNEUMONIA DI PROVINSI JAWA TIMUR - ANJAS A, MOCH.; SUKARSA, I KOMANG GDE; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika, 2019)
Geographically weighted regression (GWR) analysis is an analysis to resolve the problem with data contains effect of spatial heterogeneity. One of the problems which considers spatial heterogeneity is pneumonia. Pneumonia is spread of disease as  cause of infants’ and toddlers’ death. One of the provinces with the largest of pneumonia is East Java. The purpose of this research  is modeling of pneumonia in East Java using GWR method. The results of this research showed factors dominant and significantly of pneumonia in East Java, those factors are households of PHBS and present of measles immunization.